Dextrose Injections Across Temporomandibular Joint Mobility Disorders: A Scoping Review - Julia Kasprzycka; Maciej Chęciński; Justyna Wilk; Wojciech Macek; Maja Kosińska; Amelia Hoppe; Oliwia Jagiełło; Karolina Grzybowska-Kowalczyk; Tomasz Horodniczy; Zuzanna Baniak; Izabella Chyży; Kamila Chęcińska; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Temporomandibular joint (TMJ) mobility disorders encompass opposing clinical problems, ranging from hypermobility, subluxation, and recurrent dislocation to restricted mandibular mobility caused by disc displacement without reduction (DDwoR). Dextrose-based injections have been investigated in both settings, although their therapeutic objectives may differ. This scoping review mapped the clinical indications, injection protocols, outcomes, safety findings, and evidence gaps. Methods: PubMed/MEDLINE, Europe PMC, and BASE were searched from inception through 14 June 2026. Study selection and data charting were conducted independently by two reviewers, and primary studies underwent design-specific JBI appraisal. Results: Eighteen reports were included: 14 reports describing 13 primary clinical studies (two reports were companion publications from the same randomized pilot cohort) and four systematic reviews used for evidence mapping. Among the primary studies, twelve addressed excessive TMJ mobility, and one evaluated DDwoR with limited mouth opening. In hypermobility and recurrent dislocation, within-group reductions in pain, excessive mouth opening, and recurrence were commonly reported, but superiority over placebo or active comparators was inconsistent. In DDwoR, 5% dextrose was associated with improvements in pain, mouth opening, and chewing function, although the evidence was limited by the small sample. No serious adverse events were reported. Conclusions: Substantial heterogeneity precluded quantitative synthesis and prevented identification of an optimal protocol. Indication-specific, adequately powered randomized trials with standardized outcomes and longer follow-up are required.